Troy - Petersen, Wolfgang (Warner Bros, 2004)
Brad Pitt picks up a sword and brings a muscular, brooding presence to the role of Greek warrior Achilles in this spectacular retelling of The Iliad. Orlando Bloom and Diane Kruger play the legendary lovers who plunge the world into war, Eric Bana portrays the prince who dares to confront Achilles, and Peter O'Toole rules Troy as King Priam. Wolfgang Petersen directs, using today's technology to create a long-ago world of mighty warships, clashing armies, the massive fortress city and the towering Trojan Horse. If love is worth fighting for, it has known no greater battle than this." It's known no greater action-epic movie either.